Relationship between retinopathy and asymptomatic atherosclerosis determined by measurement of carotid intima-media thickness in patients with type 2 diabetes mellitus - İbrahim Kocaoğlu; Emine Kocaoğlu; Uğur Arslan; Mustafa Mücahit Balcı; Murat Vural; Mehmet Numan Alp; Sinan Aydoğdu (KARE Publishing, 2016)
Objective: Presence of diabetic retinopathy (DR) may be used as an early marker of atherosclerosis in type 2 diabetes mellitus (DM) patients. This study aimed to investigate the relationship between the presence of DR and carotid intimamedia thickness (CIMT), which is an indicator of early atherosclerosis in patients with type 2 DM. Methods: Thirty DM patients with retinopathy (DR group), 28 DM patients without retinopathy (non-DR group), and 27 healthy controls (control group) were included in the study. CIMT was assessed using a high-resolution B-mode ultrasonography device. Results: Mean CIMT was found to be 0.9+-0.17 mm in the DR group, 0.8+-0.16 mm in the non-DR group, and 0.7+-0.13 mm in the control group. CIMT was found to be statistically significantly higher in the DR group compared to the other 2 groups (p<0.001). When multivariate analysis was performed, presence of DR still remained as an independent risk factor for increased CIMT values. Conclusion: Presence of DR in type 2 DM patients is an independent risk factor in terms of increased CIMT, which is considered to be a finding of subclinical atherosclerosis. Therefore, we believe that type 2 DM patients with retinopathy should be closely followed in terms of cardiovascular events.